Iron and Phosphate Deficiency Regulators Concertedly Control Coumarin Profiles in Arabidopsis thaliana Roots During Iron, Phosphate, and Combined Deficiencies - Chutia, Ranju; Abel, Steffen; Ziegler, Jörg (Frontiers in Plant Science, 2019)
Plants face varying nutrient conditions, to which they have to adapt to. Adaptive responses are nutrient-specific and strategies to ensure supply and homeostasis for one nutrient might be opposite to another one, as shown for phosphate (Pi) and iron (Fe) deficiency responses, where many genes are regulated in an opposing manner. This was also observed on the metabolite levels. Whereas root and exudate levels of catechol-type coumarins, phenylpropanoid-derived 2-benzopyranones, which facilitate Fe acquisition, are elevated after Fe deficiency, they are decreased after Pi deficiency. Exposing plants to combined Pi and Fe deficiency showed that the generation of coumarin profiles in Arabidopsis thaliana roots by Pi deficiency considerably depends on the availability of Fe. Similarly, the effect of Fe deficiency on coumarin profiles is different at low compared to high Pi availability. These findings suggest a fine-tuning of coumarin profiles, which depends on Fe and Pi availability. T-DNA insertion lines exhibiting aberrant expression of genes involved in the regulation of Pi starvation responses (PHO1, PHR1, bHLH32, PHL1, SPX1) and Fe starvation responses (BRUTUS, PYE, bHLH104, FIT) were used to analyze the regulation of the generation of coumarin profiles in Arabidopsis thaliana roots by Pi, Fe, and combined Pi and Fe deficiency. The analysis revealed a role of several Fe-deficiency response regulators in the regulation of Fe and of Pi deficiency-induced coumarin profiles as well as for Pi deficiency response regulators in the regulation of Pi and of Fe deficiency-induced coumarin profiles. Additionally, the regulation of Fe deficiency-induced coumarin profiles by Fe deficiency response regulators is influenced by Pi availability. Conversely, regulation of Pi deficiency-induced coumarin profiles by Pi deficiency response regulators is modified by Fe availability.